Hak – Hak Perempuan Dalam Prespektif Gender Dan Keluarga Berencana - Khusnul Khotimah,; Verdiana Dwi Erlyna,; Syahrul Adam, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This article discusses gender equality and women's rights from an Islamic perspective. This topic also involves its application in family life and family planning (FP) programs. Patriarchal culture often places women in an unequal position, particularly in household and reproductive matters. However, Islam teaches that men and women have equal status before God. The Prophet Muhammad (peace be upon him) also exemplifies a family relationship characterized by mutual care and support. This research uses a qualitative approach, reviewing various scientific references to analyze how society constructs the roles of men and women, men's involvement in family planning, and Islamic law's perspective on birth control. The results indicate that gender equality must be achieved through a fair division of family tasks, increasing men's participation in family planning, and providing early gender education. Under Islamic law, limiting the number of children (tahdid an-nasl) is not permitted, but regulating the number of children (tanzhim an-nasl) is permitted as long as the goal is to maintain maternal health and family well-being. Therefore, realizing gender equality in family life is an important step in creating healthy, just, and happy families.